2009
DOI: 10.1177/1934578x0900400316
|View full text |Cite
|
Sign up to set email alerts
|

Novel Macrolide from Wild Strains of the Phytopathogen Fungus Colletotrichum Acutatum

Abstract: Three wild strains of C. acutatum have been investigated for their phytotoxic secondary metabolites involved in anthracnose disease. In addition to known compounds, a new macrolide 6 has been isolated and characterized by spectroscopic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…monocillins I-III, monoorden, colletodiol, etc.) with phytotoxic and antimicrobial activities including novel macrolides produced by CAsc [ 93 96 ] . DMATS are overrepresented in Colletotrichum spp.…”
Section: Discussionmentioning
confidence: 99%
“…monocillins I-III, monoorden, colletodiol, etc.) with phytotoxic and antimicrobial activities including novel macrolides produced by CAsc [ 93 96 ] . DMATS are overrepresented in Colletotrichum spp.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis of phenolic and flavonoidic antibiosis was early in all cultivars and organs. This very rapid accumulation of these constituents could be explained by their involvement in plant defense mechanisms (Broeckling et al, 2005;Suzuki et al, 2005;Naoumkina et al, 2007;Farag et al, 2009;Mancilla et al, 2009). Concerning flavonoids in particular, Chen et al (2007), Crawford et al (2004) and Calatayud et al (2011) found that resistance of cultivars of Carmellia oleifera and Lupinus angustifolius correlated with rapid and intense flavonoid production.…”
Section: Discussionmentioning
confidence: 98%
“…This is very interesting because it can improve the prospects of produce compounds such as antifouling agents or to fight against epizootics in aquaculture in the future (Zhou et al, 2014). derivatives, diaporthacol (27), which was isolated as a triacetate derivative (28) (Khamthong, et al, 2014), R-mevalonolactone (29) (Amagata et al, 1998), dothiorelone C (30) (Sommart et al, 2009), (4S, 7S, 13S) -4.7dihydroxy-1,3-tetradeca-1,5-dienolide (31) (Mancilla et al 2009), 4b-acetoxy-9b, 10b, 15a-trihydroxyprobotrydial (32) (Collado et al, 1995 and O-methyldihydrobotrydial (33) (Kimura et al, 1988) (Figure 7). The eighth these compounds were isolated from the marine-derived fungi Diaporthaceae sp.…”
Section: Sesquiterpenoidsmentioning
confidence: 99%